KAPITALISME DAN REGULASI KETENAGAKERJAAN; SEBUAH MANIFESTO BAGI PERJUANGAN KAUM BURUH - Abdul Munir (UIR PRESS, 2016)
The employemeent policy that included within the government regulation of employemeent and the another point inside it, becoming a new basic issue about the labour themself. As well as the outsourcing methods being implemented, the works relationship between labours and the one who hired them, dominantly just ended up to discrimination and exploitation to the labour rights such as: overtime payment, standart fee, the lengthen of contract fee, welfare, also the forbid about going into such thing like independent comittee of labourship.That logical point as well going to becoming a fundamental reason for the labour repressive movement into the street, to claim their rights, and express their disagremeent from the employeement policy that they claim as the reason about the abuse of their rights just like what has written before.